Promoter Methylation and Low Placental Expression of Metalloproteinase (MMP)-9, Human Leukocyte Antigen (HLA)-G, Vascular Endothelial Growth Factor (VEGF), and Highly Soluble Endoglin (sEng) as Risk Factors for Preeclampsia - Kusuma, Anak Agung Ngurah Jaya; Darmayasa, I Made; Mulyantari, Ni Kadek; Mayasari, Ni Nyoman Wistya Tri; Sutandi, Chatrine; Bay, Godefridus Paulo; Nugraha, Cokorda Gde Angga Ary (The Indonesian Biomedical Journal, 2026)
BACKGROUND: Dysregulated expressions of metalloproteinase (MMP)-9, human leucocyte antigen (HLA)-G, vascular endothelial growth factor (VEGF), and soluble endoglin (sEng) reflect impaired angiogenesis, immune tolerance, endothelial function, and trophoblast invasion that characterize abnormal placental development in preeclamptic (PE) pregnancies. However, the role of promoter methylation of these markers in linking the pathways to altered protein expression remains unclear. Hence, this study compared promoter methylation and placental expression of MMP-9, HLA-G, VEGF, and sEng between women with PE and normotensive pregnancies, and evaluate their diagnostic performance as potential biomarkers.METHODS: This case–control study included 30 women with PE and 30 controls. Placental tissue samples were collected within 15 minutes postpartum. Placental promoter methylation was assessed using methylation-specific polymerase chain reaction (PCR), and protein expression was measured using enzyme-linked immunosorbent assay (ELISA). Group differences were analyzed, diagnostic accuracy was evaluated using receiver operating characteristic (ROC) curves, and associations were expressed as adjusted odds ratios (AOR).RESULTS: Compared with controls, placentas from women with PE significantly showed higher methylation of HLA-G (58.9% vs. 37.3%) and sEng (6.7% vs. 4.1%), and lower methylation of VEGF (30.4% vs. 48.1%) and MMP-9 (36.1% vs. 44.9%). Expression of MMP-9, HLA-G, and VEGF was significantly reduced, while sEng expression was increased in PE. Multivariate analysis identified HLA-G hypermethylation (AOR 5.36), VEGF hypomethylation (AOR 8.55), sEng methylation (AOR 4.57), low expression of MMP-9, HLA-G, and VEGF, and high sEng expression (AOR 4.77) as independent predictors of PE. sEng expression demonstrated the best discrimination (AUC 0.835), followed by sEng methylation (AUC 0.785) and HLA-G methylation (AUC 0.774).CONCLUSION: PE is associated with distinct placental methylation–expression alterations, with sEng- and HLA-G–related markers showing the strongest diagnostic value.KEYWORDS: preeclampsia, DNA methylation, angiogenesis, MMP-9, HLA-G, sEng, placenta, epigenetics